Analisis Daya Tarik Produk Dodol Nanas Rosnah di Kota Dumai - Andi Riski Firnanda; Variza Aditiya (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2026)
This study aims to analyze the product attractiveness of Dodol Nanas Rosnah in Dumai City based on consumer perceptions. Micro, Small, and Medium Enterprises (MSMEs) play an important role in economic development, particularly in utilizing local agricultural resources such as pineapple. However, in an increasingly competitive market, product attractiveness plays an important role in influencing consumer purchasing decisions. This study uses a qualitative approach with a case study method to gain an in-depth understanding of consumer perceptions. Data were collected through in-depth interviews, observation, and documentation involving business owners and consumers as informants. The results show that product attractiveness is influenced by several key factors, including product quality, sensory attributes (taste, aroma, and texture), packaging design, price, and perceived value. Among these factors, taste and packaging are the most dominant aspects influencing consumer interest. Attractive packaging and distinctive taste enhance consumer preference and strengthen product competitiveness. This study implies that MSME actors need to improve both product quality and visual appeal to increase market competitiveness and consumer attraction.